PERAN INTERNATIONAL OLYMPIC COMMITTEE (IOC) DALAM MENANGANI PENGGUNAAN DOPING OLEH ATLET RUSIA PADA OLIMPIADE RIO DE JANEIRO 2016 - Pratama, Dekris; Waluyo, Tri Joko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research is aimed to explain the role of the International Olympic Committee (IOC) in handling the use of doping by Russian athletes in Rio de Janeiro 2016 Olympics. The research data is obtained from books, journals, official documents, theses, and websites. The author uses the pluralism approach and the analysis of the roles of the international organization. The method of the research is qualitative which is the data was obtained from the literature related to the research topic. The result of the research shows there was a significant role of the International Olympic Committee (IOC) in handling the use of doping by Russian athletes in the Rio de Janeiro 2016 Olympics. First, the IOC establish cooperation with the World Anti Doping Agency (WADA). From this cooperation, WADA establishes the task force that formed specially to carry out doping control by the Russian athletes. Second, the IOC provides the facilities to do a doping test. In this role, the IOC obligates all the Russian athletes must be re-tested in the WADA accredited laboratory. The IOC did not accept the result of the doping test conducted in the Moscow laboratory. Third, responding to the deceitfulness committed by Russia at the 2014 Sochi Olympics, the IOC bans Russian athletes who had competed at the 2014 Sochi Olympics to compete again at the 2016 Rio de Janeiro Olympics. IOC also suspended the Russian Olympic Committee (ROC) and the Russian Anti Doping Agency (RUSADA). This decision led to not allowing Russia to compete in the 2018 Pyeongchang Olympics. Keywords: Doping, Russia, IOC, Rio 2016 Olympics